The Application of Mirror Therapy in Ischemic Stroke Patients with Hemiparesis to Improve Upper Extremity Muscle Strength - Shafira Youanita Gunawan; Anggri Noorana Zahra (Journal of Applied Holistic Nursing Science, 2025)
Background: Ischemic stroke is one of the leading causes of disability worldwide, with hemiparesis being the most common clinical manifestation after stroke. Hemiparesis may reduce muscle strength and increase the risk of complications such as joint contractures Methods: This study aimed to evaluate the effectiveness of mirror therapy in improving upper extremity muscle strength in a 45-year-old male patient with ischemic stroke and left-sided hemiparesis. A case study design was used, with the intervention carried out over five consecutive days. The therapy consisted of adaptation exercises, basic movements, variations, and combination exercises, each repeated eight times. Results: The evaluation showed an improvement in upper extremity muscle strength from a score of 5555 | 4432 to 5555 | 4443. Additionally, there were no observed decreases in physical tolerance or therapy-related injuries. Conclusion: These findings suggest that mirror therapy is an effective, safe, and feasible rehabilitation intervention that can be implemented by nursing professionals in clinical settings for stroke patients with hemiparesis.